Bilhares planares - Andrade, Rodrigo Manoel Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
O objetivo principal deste trabalho e estudar a dinâmica de uma partícula pontual no interior de subconjuntos do plano. Tais sistemas são conhecidos na literatura como bilhares. Apresentaremos os principais conceitos desses sistemas e veremos que tais sistemas deixam invariante uma medida de probabilidade, o que nos permite aplicar a Teoria Ergódica ao problema do bilhar

The main goal of this work is to study the dynamical behavior of a point-like (dimensionless) particle in the interior of planar regions. Such systems are known in the literature as billiards. We're going to present the principal concepts of those systems and we'll see that such system turns the probability measure invariant, which allows us to apply the Ergodic Theory to billiard problems
Keywords: Teoria ergodica; Geometria; Sistemas dinâmicos diferenciais; Dynamical systems; Ergodic theory; Billiard tables; Billiard flow